Caelum et regum: studia nad symboliką państwa i władzy w polskiej literaturze i sztuce XVI i XVII stulecia - Pfeiffer, Bogusław (1960- ) (Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book focuses on the symbolical modes of representing the king and realm in the broadly understood Polish political culture of the 16th - 17th centuries. During this period the Kingdom of Poland became the Polish Commonwealth and its unique system of government, based on the three estates (King, Senate and Seym), emerged, reached its mature form and was feared to degenerate.
Keywords: literatura polska - 16-17 w.; sztuka polska - 16-17 w.; władza państwowa